MECHANICAL PROPERTIES OF RUBBER YARN WITH THE ADDITION OF KAOLIN AS A REINFORCING FILLER - Shinta Marito Siregar (Universitas Islam Negeri Sumatera Utara Medan, 2018)
Rubber yarns have been made using kaolin and titanium dioxide (TiO2) as fillers on concentrated latex compounds, with kaolin variations of 0, 6, 12, and 15 phr. This research was conducted to find out the result of kaolin concentration analysis on rubber vulcanization. The observed mechanical properties include a modulus of 300%, a modulus of 500%, a breaking tension, and a breaking extension. Kaolin mixed with titanium dioxide (TiO2) has an effect on the mechanical properties of rubber yarn. The higher the kaolin concentration, the mechanical properties of the rubber yarn are getting worse, as it is increasingly away from the standard value set for the rubber yarn.Keywords: Kaolin, rubber yarn, and vulcanization.